Evaluation of the Impact of Gender Factor in the Teaching and Inspection of Turkish Language and Literature - Emine Yağcı; Ahmet Güneyli; Havva Esra Karabacak (Tejuelo: Didáctica de la Lengua y la Literatura)
The aim of this study is to demonstrate the importance of teaching and teacher assessment of Turkish / Turkish language and literature courses and, if present, the impact that gender plays on the outcomes. The opinions of both teachers and students were taken into consideration. The research question was determined as “what is the impact of the gender of Turkish language and literature teachers and inspectors on education and inspection?” This study was conducted in north Cyprus as a case study which is a qualitative research model. The study group of the research consisted of 11 Turkish language and literature teachers employed in high schools which are operating under the General Secondary Education Office and 42 twelfth grade students attending these institutions. Interview forms were prepared for the purpose of this study using semi-structured interview techniques and content analysis was implemented during its analysis stage. In conclusion, this research revealed that gender was effective in teaching; in other words, students preferred female teachers to male teachers. However, there were no significant findings in the analysis of the data on whether teachers preferred male or female inspectors. The finding that students significantly preferred female teachers more over male teachers may have a positive role on the development of education in the future.